4(9+5m)-7m=

Simple and best practice solution for 4(9+5m)-7m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(9+5m)-7m= equation:


Simplifying
4(9 + 5m) + -7m = 0
(9 * 4 + 5m * 4) + -7m = 0
(36 + 20m) + -7m = 0

Combine like terms: 20m + -7m = 13m
36 + 13m = 0

Solving
36 + 13m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + 13m = 0 + -36

Combine like terms: 36 + -36 = 0
0 + 13m = 0 + -36
13m = 0 + -36

Combine like terms: 0 + -36 = -36
13m = -36

Divide each side by '13'.
m = -2.769230769

Simplifying
m = -2.769230769

See similar equations:

| g/200=0.011 | | -6=a/-4 | | 12y-4=9y+7 | | 2x+6=9-x | | 12y-4=9y | | x/6-15=-8 | | 5x^2y+7xy^2-5yx^2+9-9y^2x= | | x^2+19x+4=0 | | 3(x+1)=17-4x | | 3(-5+9x)-2x+1=10x-15 | | 4/5n=16/15 | | lg(lg*x)=1 | | 2.9x-7.45=5.6 | | 1/4(3X-12)-5/8X | | 12(3+y)=5(2+8) | | lg(lgx)=1 | | 1/5x90 | | 3(2X-3)=(X+19) | | 6-x=5x-9 | | y^3-4y^2+4=0 | | 3y+10x=22 | | 3m+2m+1+5m-2= | | x=8+15-3x-30+6x+8 | | -7(3x+6)-2x=3x+12 | | F(x)=2x^2+4x-9 | | -2(4+7x)=-148 | | x(x-3)/2=14 | | .5(x-3)+12= | | 9r= | | 1.80=n/100×30 | | (2x+9)+(6x+3)=180 | | 3/15x-8/15x=3 |

Equations solver categories